ELASTISITAS DEMAND DAN SUPPLY BARANG TERHADAP HARGA DI KOTA LHOKSEUMAWE (Studi Kasus atas Persepsi para Milenial) - Marzalina, Marzalina; Haryani, Haryani; Asrida, Asrida (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2024)
The research was carried out descriptively quantitatively, with a questionnaire instrument on a sample of millennials in the city of Lhokseumawe. The results of respondents' perceptions show that the law and the meaning of market demand are still low. Likewise, regarding the meaning and law of bidding, around 30% still do not understand it exactly. Regarding the theory about setting and changing commodity prices, 52% understand it and the rest don't understand it and don't bother about it. In general, the elasticity of demand and supply for the price of goods is still more than 40%, which is not yet understood precisely. The results of quantitative analysis using a statistical test approach explain that there is no significant influence between the elasticity of demand and supply on price variables.